Comparison of Financial Performance Before and After the Merger of PT. Bank Syariah Indonesia, Tbk (BSI) - Maria, Anna; Aminah, Aminah; Annisa Putri, Imanuriea; Nilwan, Afrizal (International Journal of Economics, Management and Accounting (IJEMA), 2024)
The Minister of State-Owned Enterprises announced that three state-owned sharia banks consisting of BRI Syariah, BNI Syariah and Mandiri Syariah will be integrated to form Bank Syariah Indonesia, which will be established on February 1, 2021. The unification of three sharia commercial banks under state ownership is a long wait. to create the largest sharia commercial bank with large capital is answered in this case. Finding variations in financial performance before and after the merger is the aim of this research. Capital adequacy ratio (CAR), non-performing financing (NPF), return on assets (ROA), total operating expenses and total operating income (BOPO), and loan savings ratio (FDR) are the five ratios used in this study. Quarterly financial reports from Q1 2021 to Q3 2023 after the merger, and Q2 2018 to Q4 2020 before the merger are used as samples for this research. Research findings show that Bank Syariah Indonesia's financial performance varied before and after the merger. This difference shows an increase in financial performance after the merger.